Long-term phosphorus fertilization reshapes soil microbial diversity and life-history strategies: A global meta-analysis - Jiahao Ge (22685180) (2025)
Despite broad recognition of P's importance in terrestrial ecosystems, significant gaps persist in understanding the long-term effects of P fertilization on soil microbial communities—particularly their adaptive mechanisms and evolutionary patterns under sustained P enrichment. To address this knowledge gap, we synthesized 4,087 paired observations from 194 globally distributed long-term field experiments involving P fertilization (≥3 years) across various ecosystems, including croplands, forests, and grasslands.